2012
DOI: 10.1096/fj.12-207217
|View full text |Cite
|
Sign up to set email alerts
|

The subcutaneous adipose tissue reservoir of functionally active stem cells is reduced in obese patients

Abstract: It has been demonstrated that the adipose tissue, a highly functional metabolic tissue, is a reservoir of mesenchymal stem cells. The potential use of adipose-derived stem cells (ADSCs) from white adipose tissue (WAT) for organ repair and regeneration has been considered because of their obvious benefits in terms of accessibility and quantity of available sample. However, the functional capability of ADSCs from subjects with different adiposity has not been investigated. It has been our hypothesis that ADSCs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 58 publications
8
101
0
5
Order By: Relevance
“…3). We have found data about altered genomic instability [130], telomere attrition [89, 131], epigenetic alterations [132], loss of proteostasis and deregulated nutrients [88], mitochondrial dysfunction [133, 134], cellular senescence and stem cell exhaustion [85] and altered cell communication [135]. Along this line, different studies using heterochronic parabiosis experiments elegantly demonstrated that environmental factors influence stem cell functions [136]; exposure of stem cells to systemic factors from young mice increased their proliferative capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). We have found data about altered genomic instability [130], telomere attrition [89, 131], epigenetic alterations [132], loss of proteostasis and deregulated nutrients [88], mitochondrial dysfunction [133, 134], cellular senescence and stem cell exhaustion [85] and altered cell communication [135]. Along this line, different studies using heterochronic parabiosis experiments elegantly demonstrated that environmental factors influence stem cell functions [136]; exposure of stem cells to systemic factors from young mice increased their proliferative capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The negative effects of obesity on stem cells described are numerous. Subcutaneous adipose tissue from obese patients has a diminished reservoir of functionally active stem cells [85]. Moreover, metabolism and maturation of APCs are arrested in an obese environment [17], and their ability to migrate or invade a tissue is impaired [86, 87].…”
Section: Stem Cell Behavior In Different Diseasesmentioning
confidence: 99%
“…Strikingly, just as the ageing milieu compromises satellite cell function and muscle regeneration (Brack et al, 2007;Conboy et al, 2005), obesity-related perturbation of cytokine activity impedes tissue repair following injury, as evidenced by delayed wound repair and impaired myofibroblast differentiation (Seitz et al, 2010). Similarly, just as exposing mouse satellite cells to the ageing milieu skews the lineage of satellite cells away from myogenic lineages (Brack et al, 2007), adipose-derived mesenchymal stem cells isolated from obese humans have reduced differentiation potential in ex vivo functional assays and therefore have lower capacity for spontaneous or therapeutic repair, when compared to stem cells derived from non-obese metabolically normal individuals (Onate et al, 2012).…”
Section: The Impact Of Obesity On Stem Cell Functionmentioning
confidence: 99%
“…The number of studies in this area of research remains still limited whatever the species considered (Mihaylova et al, 2014). Recently, it has been reported that transcriptomic profiles and properties of stem cells isolated from subcutaneous adipose tissue were different in obese patients compared with non-obese individuals (Oñate et al, 2012;. Taken together, these studies support the view that flexibility of adult stem cells in response to external changes deserves to be further investigated.…”
Section: Prenatal and Postnatal Growth Of Adipose Tissuesmentioning
confidence: 58%